2020
DOI: 10.1186/s12888-020-02848-x
|View full text |Cite
|
Sign up to set email alerts
|

Adult ADHD screening scores and hospitalization due to pedestrian injuries: a case-control study

Abstract: Abstracts Background The aim of this study was to investigate the association between adult ADHD screening scores and hospitalization due to pedestrian injuries in a sample of Iranian pedestrians. Methods Through a case-control study, a case population of 177 pedestrians injured by the vehicles in road traffic crashes were compared with 177 controls who lacked a record of intentional or unintentional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(63 reference statements)
0
2
1
Order By: Relevance
“…Though previous research is scarce in relation to the mechanisms that might underpin an association between ADHD feature domains and suicidality, these findings corroborate the relationship between hyperactive/impulsive features and a range of behaviours and outcomes that might serve to desensitise individuals to pain and fear of death, including NSSI, [57][58][59] abusing substances and other risky behaviours, 76 getting accidentally injured or involved in accidents. 77,78 While we did not predict significant associations between inattentive features and our mediators, it is important to note that these features are, in fact, also associated with risky behaviour, accident and injury, and suicide itself in people with ADHD. 20,78,79 It is likely that this association is underpinned by different mechanisms, such as difficulties with cognitive control as opposed to sensation-seeking.…”
Section: Discussioncontrasting
confidence: 55%
“…Though previous research is scarce in relation to the mechanisms that might underpin an association between ADHD feature domains and suicidality, these findings corroborate the relationship between hyperactive/impulsive features and a range of behaviours and outcomes that might serve to desensitise individuals to pain and fear of death, including NSSI, [57][58][59] abusing substances and other risky behaviours, 76 getting accidentally injured or involved in accidents. 77,78 While we did not predict significant associations between inattentive features and our mediators, it is important to note that these features are, in fact, also associated with risky behaviour, accident and injury, and suicide itself in people with ADHD. 20,78,79 It is likely that this association is underpinned by different mechanisms, such as difficulties with cognitive control as opposed to sensation-seeking.…”
Section: Discussioncontrasting
confidence: 55%
“…The matching criteria in this study were age and sex as in other studies. 19 , 20 After calculating the required sample size of 597, computerized random sampling in Stata 15 software was used to select 199 cases for 398 controls ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Many studies have been published on association of ADHD and accidents, the majority of which have shown that there is an increased likelihood of accidents and trauma among those suffering from ADHD both at childhood and adult age. [5][6][7][8][9][10][11] Various types of trauma and accidents have been investigated in this regard including burn injuries, fall injuries, motorcycle injuries, traffic injuries, and injuries as a whole.…”
Section: Introductionmentioning
confidence: 99%